(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
The article describes the theoretical and pedagogical foundations of practical teacher training in history in Chile, as expressed in the training documents of five universities, which in turn is referenced with public policy on teacher training. Methodologically, we resorted to documentary analysis from a comprehensive/interpretative perspective using Atlas Ti software, version 7.5. From a process of progressive coding, categories of analysis emerged that allowed for the construction of the main findings. The results show the importance assigned to the practical training line by the universities in their curricular documents. However, there is evidence of the absence of models for reflection, scant consideration of the knowledge and know-how derived from practical experience and the secondary role assigned to teacher guides, who are key players in the process.